Deletion of arrestin-3 does not reduce drug-seeking behavior in a longitudinal paradigm of oral morphine self-administration - Gooding, Sarah Warren; Felth, Lindsey; Foxall, Randi; Rosa, Zachary; Ireton, Kyle; Sall, Izabella; Gipoor, Joshua; Gaur, Anirudh; King, Madeline; Dirks, Noah; Whistler, Cheryl Allyne; Whistler, Jennifer Lynne (Frontiers in Pharmacology, 2024)
Introduction: Opioid drugs are potent analgesics that mimic the endogenous opioid peptides, endorphins and enkephalins, by activating the µ-opioid receptor. Opioid use is limited by side effects, including significant risk of opioid use disorder. Improvement of the effect/side effect profile of opioid medications is a key pursuit of opioid research, yet there is no consensus on how to achieve this goal. One hypothesis is that the degree of arrestin-3 recruitment to the µ-opioid receptor impacts therapeutic utility. However, it is not clear whether increased or decreased interaction of the µ-opioid receptor with arrestin-3 would reduce compulsive drug-seeking. Methods: We utilized three genotypes of mice with varying abilities to recruit arrestin-3 to the µopioid receptor in response to morphine in a novel longitudinal operant self-administration model. We also created a quantitative method to define compulsivity in drug-seeking based on a multivariate analysis of several operant response variables. Results: We demonstrate that arrestin-3 knockout and wild type mice have highly variable drugseeking behavior with few genotype differences. In contrast, in mice where the µ-opioid receptor strongly recruits arrestin-3, drug-seeking behavior is much less varied. We found that mice lacking arrestin-3 were more likely to meet the criteria for compulsivity whereas mice with enhanced arrestin-3 recruitment did not develop a compulsive phenotype. Conclusion: These experiments show that a lack of arrestin-3 is not protective against the abuse liability of morphine in an operant self-administration context. Our data also suggest that opioids that engage both G protein and arrestin-3, recapitulating the endogenous signaling pattern, will reduce abuse liability.